Aerated concrete block and preparation method thereof

By using specific proportions of raw materials in aerated concrete blocks, forming a porous structure and using modified materials to improve mechanical properties, the problem of low compressive strength of aerated concrete blocks is solved, and higher compressive strength and durability are achieved.

CN119874279APending Publication Date: 2025-04-25QINGDAO TIANLI XINGDA NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411927525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Due to the porous structure, aerated concrete blocks have low compressive strength, which is difficult to meet the strength and durability requirements of building materials.

Method used

Raw materials with specific ratios are used, including silicate cement, sand, aluminum powder, polycarboxylic acid water reducing agent, lime, modified waste glue powder, hollow glass microbeads and modified polystyrene fibers, to form a porous structure through hydration and foaming reactions, and at the same time, the mechanical properties of the block are improved by modified materials.

Benefits of technology

It significantly improves the compressive strength and durability of aerated concrete blocks, enhances its thermal insulation, sound insulation and thermal insulation properties, and extends the service life of the building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209574660000091
    Figure BDA0005209574660000091
  • Figure BDA0005209574660000101
    Figure BDA0005209574660000101
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly discloses an aerated concrete block and a preparation method thereof. The aerated concrete block is prepared from the following raw materials in parts by weight: 70 to 80 parts of water, 25 to 30 parts of Portland cement, 30 to 35 parts of sand, 3 to 5 parts of aluminum powder, 1 to 3 parts of polycarboxylate superplasticizer, 7 to 9 parts of lime, 10 to 15 parts of modified waste rubber powder, 10 to 12 parts of hollow glass beads and 12 to 16 parts of modified polystyrene fiber. The aerated concrete block prepared in the invention has good strength, compactness and tensile strength, and the strength, durability and stability of the aerated concrete block are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete technology, and in particular to an aerated concrete block and a preparation method thereof. Background Art

[0002] Aerated concrete blocks, also known as aerated concrete lightweight bricks or aerated bricks, are a lightweight, porous building material. They are mainly made by mixing raw materials such as cement, lime, sand, aluminum powder and water, and then undergoing processes such as gasification, pouring, cutting and autoclaving. They are simple to prepare and widely used.

[0003] Aerated concrete blocks are lightweight, heat-insulating, fire-resistant and durable, and are widely used in building walls, partitions, insulation layers and sound insulation layers. However, due to their porous structure, aerated concrete blocks reduce their density and thus their compressive strength. Summary of the invention

[0004] In order to improve the problem of low compressive strength of concrete blocks, the present application provides an aerated concrete block and a preparation method thereof.

[0005] The present application provides an aerated concrete block, which adopts the following technical solution: An aerated concrete building block comprises the following raw materials, measured by weight: 70-80 parts of water, 25-30 parts of silicate cement, 30-35 parts of sand, 3-5 parts of aluminum powder, 1-3 parts of polycarboxylic acid water reducer, 7-9 parts of lime, 10-15 parts of modified waste rubber powder, 10-12 parts of hollow glass microspheres, and 12-16 parts of modified polystyrene fibers.

[0006] By adopting the above technical solution, when silicate cement reacts with water, calcium hydroxide is generated. Aluminum powder acts as a foaming agent and reacts with calcium hydroxide to generate hydrogen. Hydrogen forms a large number of tiny bubbles in the concrete mixture. These bubbles are fixed during the concrete hardening process to form a porous structure of aerated concrete, giving aerated concrete good thermal insulation, sound insulation and heat insulation properties. Sand, as a filling material for aerated concrete blocks, together with cement and aluminum powder, constitutes the basic skeleton of the blocks, increases the density of the blocks, and improves their structural stability.

[0007] Water reducers can significantly improve the fluidity of concrete mixtures, making it easier for concrete to flow and fill molds during the pouring process, thereby improving production efficiency and the uniformity of blocks. Lime reacts with water to form calcium hydroxide, which releases heat and increases the alkaline environment of the mixture. Calcium hydroxide further reacts with the silicate component in silicate cement to accelerate the hardening process of cement, forming a more solid cementitious structure and improving the strength, durability and stability of aerated concrete blocks.

[0008] Modified waste rubber powder has good thermal insulation performance, which can improve the thermal resistance of the blocks and enhance their thermal insulation effect. In addition, the elastic properties of waste rubber powder can improve the toughness of aerated concrete blocks, making them less likely to crack when subjected to external forces, thereby improving the impact resistance of the blocks. Hollow glass microspheres have high strength and can disperse the stress inside aerated concrete. They are combined with modified waste rubber powder and sand to improve the compressive strength of the blocks. Modified polystyrene fiber has good tensile strength and elasticity, which can effectively disperse the stress inside aerated concrete, reduce cracks caused by drying shrinkage or temperature changes, and improve the crack resistance of the blocks. It also has good toughness, which can enhance the toughness of aerated concrete blocks, making them less likely to break when subjected to external forces, thereby improving the impact resistance of the blocks.

[0009] Modified polystyrene fibers are distributed in silicate cement and evenly mixed with sand, modified waste rubber powder and hollow glass beads. The modified waste rubber powder can be loaded on the surface of modified polystyrene fibers, which improves the strength and toughness of modified polystyrene fibers. Various components cooperate with each other to help reduce microcracks inside the blocks, improve their durability and extend the service life of the building.

[0010] Preferably, the method for preparing the modified waste rubber powder comprises the following steps: (1) dispersing the waste rubber powder in a sodium hydroxide solution, stirring at a temperature of 50-55° C. for 10-15 minutes, washing with water, and then dispersing in deionized water, adding a silane coupling agent, stirring for 20-24 minutes, filtering, and drying to obtain pretreated waste rubber powder; (2) heating the nano-silica at 150-160° C. for 1-2 h, dispersing the nano-silica in an ethanol solution, adding hydrochloric acid, stirring for 1-2 h, washing with water, and drying to obtain pretreated nano-silica; (3) Dispersing the pretreated waste rubber powder in step (1) in deionized water, adding the pretreated nano-silicon dioxide and modified kaolin in step (2), stirring at a temperature of 80-85° C. for 2-3 hours, drying, and grinding to obtain modified waste rubber powder.

[0011] By adopting the above technical solution, the sulfide in the waste rubber powder can be decomposed in the alkaline environment of sodium hydroxide, thereby removing the sulfide, reducing the harmful components in the waste rubber powder, improving the porosity of the waste rubber powder, increasing the adsorption of the waste rubber powder, and facilitating mixing with other components. When mixed with a silane coupling agent, the silane coupling agent can react with the active groups on the surface of the waste rubber powder to form a chemical bond, thereby improving the bonding strength between the waste rubber powder and other components, helping to evenly disperse the waste rubber powder in the matrix material, avoiding agglomeration, and improving the uniformity and stability of the system.

[0012] The surface of nano-silica is treated with hydrochloric acid to reduce the surface energy of nano-silica, improve the dispersibility and stability of nano-silica, help load nano-silica in the pores of modified kaolin, and improve the strength of the system. Waste rubber powder can adhere to the surface of nano-silica. The combination of waste rubber powder, nano-silica and modified kaolin improves the mechanical properties of the system such as tensile strength, compressive strength and flexural strength. The addition of nano-silica and modified kaolin can form a micro-nano composite structure to enhance the rigidity and toughness of the system.

[0013] Preferably, the mass ratio of the waste rubber powder, nano-silicon dioxide and modified kaolin is 1:0.4-0.6:0.1-0.2.

[0014] By adopting the above technical scheme, the mass ratio of waste rubber powder, nano-silicon dioxide and modified kaolin is further limited within a certain range, and the mechanical properties of the system are improved. The waste rubber powder has good elasticity and mechanical strength, the nano-silicon dioxide has good wear resistance, strength and corrosion resistance, and the modified kaolin has certain viscosity and density. The waste rubber powder, nano-silicon dioxide and modified kaolin are combined to improve the compressive strength and flexural strength of aerated concrete blocks, enhance their overall mechanical properties, and also improve the crack resistance of aerated concrete blocks, reduce cracking caused by temperature changes or humidity changes, and improve the durability of the blocks.

[0015] Preferably, the preparation method of the modified kaolin comprises the following steps: calcining kaolinite at a temperature of 800-900°C for 5-6h, dispersing it in deionized water, adding wood ash, acetic acid and chitosan, stirring at a temperature of 70-75°C for 1-2h, drying, and grinding to obtain modified kaolin.

[0016] By adopting the above technical solution, kaolin is first calcined, so that the layered structure of kaolinite begins to change, and some water molecules are expelled, causing its lattice structure to change, forming a more stable semi-crystalline structure, thereby improving the hardness, wear resistance, and compressive strength of kaolinite, and improving the chemical stability of kaolinite, making it less likely to undergo chemical reactions in acidic and alkaline environments, and suitable for industrial applications that require chemical stability.

[0017] Wood ash can be loaded on the surface and pore structure of kaolin, increasing the specific surface area of ​​kaolin and the adsorption capacity of kaolin. Kaolin is subsequently used in aerated concrete blocks to improve the density of aerated concrete blocks, thereby improving their impermeability and corrosion resistance. Moreover, silicon, calcium and other components in wood ash can react with cement hydration products to form stable compounds such as calcium silicate, thereby improving the compressive strength and flexural strength of aerated concrete blocks.

[0018] Chitosan has a certain viscosity, which allows wood ash to adhere to the surface of kaolin, improving the stability and mechanical properties of the modified kaolin structure. It is subsequently applied to aerated concrete blocks to enhance the internal structure of aerated concrete blocks and improve their compressive strength and flexural strength.

[0019] Preferably, the method for preparing the modified polystyrene fiber comprises the following steps: (1) dispersing polystyrene fibers in hydrogen peroxide, stirring for 10-13 minutes, washing with water, and then dispersing in deionized water, adding fatty acid polyoxyethylene ester, stirring for 1-2 hours, filtering, and drying to obtain pretreated polystyrene fibers; (2) dispersing the loofah fibers in a sodium hydroxide solution, adding graphene, stirring at a temperature of 97-99° C. for 12-16 min, filtering, drying, and crushing to obtain pretreated loofah fibers; (3) Dispersing the pretreated polystyrene fiber in step (1) in deionized water, adding the pretreated loofah fiber and ethyl cellulose in step (2), stirring at a temperature of 80-85° C. for 2-3 hours, filtering, and drying to obtain modified polystyrene fiber.

[0020] By adopting the above technical scheme, hydrogen peroxide erodes the surface of the polystyrene fiber to a certain extent, thereby increasing the specific surface area of ​​the polystyrene fiber and the porosity of the polystyrene fiber. Fatty acid polyoxyethylene ester further modifies the surface of the polystyrene fiber and increases the surface activity and hydrophilicity of the polystyrene fiber, thereby improving the compatibility and adhesion of the polystyrene fiber with other materials.

[0021] Sodium hydroxide treatment can remove wax and impurities on the surface of loofah fibers, improve the adsorption of loofah fibers, help load graphene on the surface and pore structure of loofah fibers, increase the mechanical properties of loofah fibers, such as tensile strength, compressive strength and elastic modulus, and subsequently improve the mechanical properties of aerated concrete blocks.

[0022] Pretreated polystyrene fiber, treated loofah fiber and ethyl cellulose are mixed. Ethyl cellulose has a certain viscosity, so that the treated loofah fiber is loaded on the surface of the pretreated polystyrene fiber, thereby improving the mechanical properties of the pretreated polystyrene fiber. Styrene fiber has high strength and elasticity, and loofah fiber has good tensile properties. Ethyl cellulose can be used as a binder. After the three are mixed, the mechanical properties of the composite material, such as tensile strength, compressive strength and elastic modulus, can be significantly improved.

[0023] Preferably, the mass ratio of the polystyrene fiber, the loofah fiber and the ethyl cellulose is 1:0.5-0.7:0.2-0.3.

[0024] By adopting the above technical scheme, the mass ratio of polystyrene fiber, loofah fiber and ethyl cellulose is further limited within a certain range, so as to improve the mechanical properties, wear resistance and crack resistance of polystyrene fiber, loofah fiber is loaded on the surface of polystyrene fiber, ethyl cellulose makes polystyrene fiber and loofah fiber bond tightly, so that the performance of modified polystyrene fiber is stable, styrene fiber has high strength and elasticity, loofah fiber has good tensile properties, ethyl cellulose can be used as adhesive, and after mixing the three, the tensile strength, compressive strength, tear resistance and other mechanical properties of composite materials can be significantly improved, and the corresponding performance of aerated concrete blocks can be subsequently improved.

[0025] Preferably, the mass ratio of the polystyrene fiber, polyoxyethylene fatty acid ester and graphene is 1g:0.1-0.2g:10-15mg.

[0026] By adopting the above technical scheme, the mass ratio of polystyrene fiber, fatty acid polyoxyethylene ester and graphene is further limited within a certain range, thereby improving the mechanical properties and wear resistance of polystyrene fiber. Fatty acid polyoxyethylene ester is used to modify the surface of polystyrene fiber to improve the surface activity and adsorption of polystyrene fiber, so that part of graphene can be loaded on the surface of polystyrene fiber, thereby improving the strength and toughness of polystyrene fiber. The subsequent application in aerated concrete blocks improves the strength and tear resistance of the system, making it less likely to be damaged when subjected to external forces.

[0027] Preferably, the lime is medium-speed lime, and the calcium oxide content is ≥80% (by mass).

[0028] By adopting the above technical scheme, the conditions of lime are further limited, ensuring the high purity and high activity of lime, and applying it to aerated concrete blocks to improve the density of aerated concrete blocks, enhance their impermeability and freeze-thaw resistance, and extend their service life.

[0029] Preferably, the water reducer is a polycarboxylate water reducer.

[0030] By adopting the above technical solution, polycarboxylate water-reducing agent can improve the fluidity of aerated concrete mixture, making it easier to operate during the pouring process and improving production efficiency; it helps to improve the strength and density of concrete while reducing the risk of shrinkage and cracking, and can also improve the impermeability and freeze-thaw resistance of aerated concrete blocks and extend their service life.

[0031] In the second aspect, the present application also provides a method for preparing an aerated concrete block, comprising the following steps: grinding sand, mixing it evenly with water, silicate cement, and a water reducer, adding aluminum powder, continuing to stir, and then adding lime, modified waste rubber powder, hollow glass microbeads, and modified polystyrene fiber, stirring for 10-15 minutes to obtain concrete, pouring the concrete slurry into a mold, letting it stand for 12-14 hours, cutting to obtain a block brick body, and steaming the block brick body to obtain an aerated concrete block.

[0032] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which is helpful to improve the efficiency of preparing aerated concrete blocks, and the obtained aerated concrete blocks have good mechanical properties.

[0033] In summary, this application has the following beneficial effects: 1. The modified waste rubber powder in this application improves the toughness of aerated concrete blocks, making them less likely to crack when subjected to external forces, and improving the impact resistance of the blocks. Hollow glass microspheres have high strength and can disperse the stress inside aerated concrete, and cooperate with modified waste rubber powder and sand to improve the compressive strength of the blocks.

[0034] 2. In the present application, the modified polystyrene fiber is distributed in silicate cement and evenly mixed with sand, modified waste rubber powder and hollow glass beads. The modified waste rubber powder can be loaded on the surface of the modified polystyrene fiber, thereby improving the strength and toughness of the modified polystyrene fiber. The various components cooperate with each other, which helps to reduce microcracks inside the blocks, improve their durability and extend the service life of the building.

[0035] 3. In the present application, when silicate cement reacts with water to generate calcium hydroxide, aluminum powder acts as a foaming agent and reacts with calcium hydroxide to generate hydrogen. Hydrogen forms a large number of tiny bubbles in the concrete mixture, forming a porous structure of aerated concrete, which gives the aerated concrete good thermal insulation, sound insulation and heat insulation properties. Together with sand, cement and aluminum powder, it constitutes the basic skeleton of the block, increases the density of the block and improves its structural stability. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0038] Preparation example of modified waste rubber powder Preparation Example 1-1 The preparation method of modified waste rubber powder comprises the following steps: (1) 20 kg of waste rubber powder was dispersed in 25 L of 20% sodium hydroxide solution, stirred at 55° C. for 15 min, washed with water, and then dispersed in 27 L of deionized water, 2 kg of silane coupling agent KH550 was added, stirred for 22 min, filtered, and dried to obtain pretreated waste rubber powder; (2) heating the nano-silica at 160° C. for 2 h, dispersing it in 12 L of 75% ethanol solution, adding 2 L of hydrochloric acid, stirring it for 2 h, washing it with water, and drying it to obtain pretreated nano-silica; (3) Disperse the pretreated waste rubber powder in step (1) in 50 L of deionized water, add the pretreated nano-silicon dioxide and modified kaolin in step (2), stir at 85° C. for 3 h, dry, and grind to obtain modified waste rubber powder.

[0039] The mass ratio of waste rubber powder, nano-silicon dioxide and modified kaolin is 1:0.4:0.2.

[0040] The preparation method of modified kaolin includes the following steps: calcining 6 kg of kaolinite at a calcination temperature of 850° C. for 6 hours, dispersing the calcined kaolinite in 8 L of deionized water, adding 1 kg of wood ash, 2 L of acetic acid solution with a mass fraction of 12%, and 0.8 kg of chitosan, stirring the mixture at a temperature of 75° C. for 2 hours, drying, and grinding the mixture to obtain modified kaolin.

[0041] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no nano-silicon dioxide is added.

[0042] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified kaolin is added.

[0043] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of waste rubber powder, nano-silicon dioxide and modified kaolin is 1:0.6:0.1.

[0044] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of waste rubber powder, nano-silicon dioxide and modified kaolin is 1:0.1:0.5.

[0045] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no wood ash is added in the preparation method of modified kaolin.

[0046] Preparation Example 1-7 The difference from Preparation Example 1-1 is that chitosan is not added in the preparation method of modified kaolin.

[0047] Preparation example of modified polystyrene fiber Preparation Example 2-1 The preparation method of modified polystyrene fiber comprises the following steps: (1) 20 kg of polystyrene fibers were dispersed in 25 L of hydrogen peroxide, stirred for 13 min, washed with water, and then dispersed in 30 L of deionized water, 2 kg of fatty acid polyoxyethylene ester was added, stirred for 2 h, filtered, and dried to obtain pretreated polystyrene fibers; (2) dispersing the loofah fibers in 20 L of a 15% sodium hydroxide solution, adding graphene, stirring at 99° C. for 16 min, filtering, drying, and crushing to obtain pretreated loofah fibers; (3) The polystyrene fiber pretreated in step (1) is dispersed in 55 L of deionized water, and the loofah fiber pretreated in step (2) and ethyl cellulose are added, stirred at a temperature of 85° C. for 3 h, filtered, and dried to obtain modified polystyrene fiber.

[0048] The mass ratio of polystyrene fiber, loofah fiber and ethyl cellulose is 1:0.5:0.2.

[0049] The mass ratio of polystyrene fiber, fatty acid polyoxyethylene ester and graphene is 1g:0.2g:10mg.

[0050] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), loofah fiber is not added.

[0051] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), ethyl cellulose is not added.

[0052] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of polystyrene fiber, loofah fiber and ethyl cellulose is 1:0.7:0.3.

[0053] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of polystyrene fiber, loofah fiber and ethyl cellulose is 1:0.1:0.6.

[0054] Preparation Example 2-6 The difference from Preparation Example 2-1 is that in step (2), no fatty acid polyoxyethylene ester is added.

[0055] Preparation Example 2-7 The difference from Preparation Example 2-1 is that in step (2), no graphene is added.

[0056] Preparation Example 2-8 The difference from Preparation Example 2-1 is that the mass ratio of polystyrene fiber, polyoxyethylene fatty acid ester and graphene is 1g:0.1g:15mg.

[0057] Preparation Example 2-9 The difference from Preparation Example 2-1 is that the mass ratio of polystyrene fiber, polyoxyethylene fatty acid ester and graphene is 1g:0.6g:5mg. Example

[0058] Example 1 An aerated concrete block includes the following raw materials by weight: 70 kg of water, 25 kg of silicate cement, 30 kg of sand, 3 kg of aluminum powder, 1 kg of water reducing agent, 7 kg of lime, 10 kg of modified waste rubber powder, 10 kg of hollow glass microspheres, and 16 kg of modified polystyrene fiber; The lime is medium-speed lime with a calcium oxide content of ≥80% (mass), and the water reducer is a polycarboxylic acid water reducer.

[0059] The preparation method of the aerated concrete building block comprises the following steps: grinding sand into a fineness of 250 mesh, mixing it evenly with water, silicate cement and polycarboxylic acid water reducer, adding aluminum powder, continuing to mix evenly, then adding lime, modified waste rubber powder, hollow glass microspheres and modified polystyrene fiber, mixing for 15 minutes to obtain concrete, pouring the concrete slurry into a mold, standing it for 12 hours, cutting it to obtain a building block brick body, steaming the building block brick body to obtain an aerated concrete building block.

[0060] Steaming conditions: steaming temperature is 170℃, steaming pressure is 1.2MPa, and steaming time is 7h.

[0061] The modified waste rubber powder was prepared by using Preparation Example 1-1; and the modified polystyrene fiber was prepared by using Preparation Example 2-1.

[0062] Example 2 An aerated concrete block, which differs from Example 1 in that, by weight, it comprises the following raw materials: 80 kg of water, 30 kg of silicate cement, 35 kg of sand, 5 kg of aluminum powder, 3 kg of water reducing agent, 9 kg of lime, 15 kg of modified waste rubber powder, 12 kg of hollow glass microspheres, and 12 kg of modified polystyrene fiber.

[0063] Example 3 An aerated concrete block, which is different from Example 1 in that the modified waste rubber powder is prepared using Preparation Example 1-2.

[0064] Example 4 An aerated concrete block, which is different from Example 1 in that the modified waste rubber powder is prepared using Preparation Examples 1-3.

[0065] Example 5 An aerated concrete block, which is different from Example 1 in that the modified waste rubber powder is prepared using Preparation Examples 1-4.

[0066] Example 6 An aerated concrete block, which is different from Example 1 in that the modified waste rubber powder is prepared using Preparation Examples 1-5.

[0067] Example 7 An aerated concrete block, which is different from Example 1 in that the modified waste rubber powder is prepared using Preparation Examples 1-6.

[0068] Example 8 An aerated concrete block, which is different from Example 1 in that the modified waste rubber powder is prepared using Preparation Examples 1-7.

[0069] Example 9 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Example 2-2.

[0070] Example 10 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Example 2-3.

[0071] Embodiment 11 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Examples 2-4.

[0072] Example 12 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Examples 2-5.

[0073] Example 13 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Examples 2-6.

[0074] Embodiment 14 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Examples 2-7.

[0075] Embodiment 15 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Examples 2-8.

[0076] Example 16 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is prepared using Preparation Examples 2-9.

[0077] Comparative Example Comparative Example 1 An aerated concrete building block, which is different from Example 1 in that no modified waste rubber powder is added.

[0078] Comparative Example 2 An aerated concrete building block, which is different from Example 1 in that the modified waste rubber powder is replaced by an equal amount of modified waste rubber powder.

[0079] Comparative Example 3 An aerated concrete block, which is different from Example 1 in that modified polystyrene fiber is not added.

[0080] Comparative Example 4 An aerated concrete block, which is different from Example 1 in that the modified polystyrene fiber is replaced by an equal amount of polystyrene fiber.

[0081] Performance testing The aerated concrete blocks prepared in Examples 1-16 and Comparative Examples 1-4 were subjected to performance tests. The compressive strength, dry density, and post-freezing compressive strength were tested in accordance with GB / T11968-2020. The test results are shown in Table 1.

[0082] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the concrete prepared in Examples 1-2, 5, 11 and 15 of the present application has good mechanical properties and mechanical strength. Among them, the compressive strength of Example 1 reaches 17.3 MPa at 1 day, 30.8 MPa at 7 days, and 43.5 MPa at 14 days. The dry density is 690 kg / m 3 The tensile strength is 2.35MPa and the post-freezing compressive strength is 40.2MPa, which indicates that the prepared aerated concrete blocks have good mechanical properties and mechanical strength. The various components cooperate with each other, which helps to reduce the micro cracks inside the blocks, improve the strength and durability of the blocks, and extend the service life of the building.

[0083] In the preparation method of the modified scrap rubber powder in Example 3, nano-silicon dioxide is not added; in the preparation method of the modified scrap rubber powder in Example 4, modified kaolin is not added; in Example 6, the masses of the scrap rubber powder, nano-silicon dioxide and modified kaolin are changed. As can be seen from Table 1, compared with Example 1, the test results of the compressive strength, dry density, tensile strength and post-freezing compressive strength of Examples 3-4 at 1 day, 7 days and 14 days are significantly worse than those of Example 1 and Example 5, while the performance test of Example 6 is better than that of Examples 3-4, but worse than that of Example 1 and Example 5, indicating that nano-silicon dioxide has good wear resistance, strength and corrosion resistance, and modified kaolin has certain viscosity and compactness. The combination of scrap rubber powder, nano-silicon dioxide and modified kaolin improves the compressive strength and flexural strength of aerated concrete blocks, enhances their overall mechanical properties, and also improves the crack resistance of aerated concrete blocks, reduces cracking caused by temperature changes or humidity changes, and improves the durability of blocks.

[0084] In the preparation method of modified kaolin in Examples 7-8, wood ash and chitosan are not added respectively. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, dry density, tensile strength and post-freezing compressive strength of Examples 7-8 at 1 day, 7 days and 14 days are significantly better than those of Example 4, but worse than those of Example 1 and Example 5, indicating that chitosan has a certain viscosity, so that wood ash adheres to the surface of kaolin, improves the stability and mechanical properties of the modified kaolin structure, and is subsequently applied to aerated concrete blocks to enhance the internal structure of aerated concrete blocks and improve their compressive strength and flexural strength.

[0085] In the preparation method of modified polystyrene fiber in Example 9, loofah fiber is not added, in the preparation method of modified polystyrene fiber in Example 10, ethyl cellulose is not added, and in Example 12, the masses of polystyrene fiber, loofah fiber and ethyl cellulose are changed. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, dry density, tensile strength and post-freezing compressive strength of Examples 9-10 at 1 day, 7 days and 14 days are significantly worse than those of Example 1 and Example 11, while the performance test of Example 12 is better than that of Examples 9-10, but worse than that of Examples 1 and Example 11, indicating that styrene fiber has higher strength and elasticity, loofah fiber has good tensile properties, and ethyl cellulose can be used as a binder. After mixing the three, the mechanical properties of the composite material such as tensile strength, compressive strength and tear resistance can be significantly improved, and the corresponding properties of the aerated concrete block can be subsequently improved.

[0086] In the preparation method of modified polystyrene fiber in Example 13, no fatty acid polyoxyethylene ester is added; in the preparation method of modified polystyrene fiber in Example 14, no graphene is added; and in Example 16, the masses of polystyrene fiber, fatty acid polyoxyethylene ester and graphene are changed. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, dry density, tensile strength and post-freezing compressive strength of Examples 13-14 at 1 day, 7 days and 14 days are significantly worse than those of Example 1 and Example 15, while the performance test of Example 16 is better than that of Examples 13-14, but worse than that of Examples 1 and Example 15, indicating that fatty acid polyoxyethylene ester performs surface modification on polystyrene fiber, improves the surface activity and adsorption of polystyrene fiber, enables part of graphene to be loaded on the surface of polystyrene fiber, improves the strength and toughness of polystyrene fiber, and is subsequently applied to aerated concrete blocks, thereby improving the strength and tear resistance of the system, making it less susceptible to damage when subjected to external forces.

[0087] No modified waste rubber powder or modified polystyrene fiber is added to Comparative Example 1 and Comparative Example 3, respectively. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, dry density, tensile strength and post-freezing compressive strength of Comparative Example 1 and Comparative Example 3 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2, indicating that the modified waste rubber powder improves the toughness of the aerated concrete block, making it less likely to crack when subjected to external force, thereby improving the impact resistance of the block; the modified polystyrene fiber has good tensile strength and elasticity, can effectively disperse the stress inside the aerated concrete, reduce cracks caused by drying shrinkage or temperature changes, and improve the crack resistance and impact resistance of the block.

[0088] In Comparative Examples 2 and 4, the modified waste rubber powder was replaced by an equal amount of modified waste rubber powder, and the modified polystyrene fiber was replaced by an equal amount of polystyrene fiber. It can be seen from Table 1 that, compared with Example 1, the test results of 1-day, 7-day and 14-day compressive strength, dry density, tensile strength and post-freezing compressive strength of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified waste rubber powder and modified polystyrene fiber in the present application have better mechanical properties, thereby improving the mechanical properties of the building blocks.

[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An aerated concrete block, characterized in that: The raw materials are as follows, measured by weight: 70-80 parts of water, 25-30 parts of silicate cement, 30-35 parts of sand, 3-5 parts of aluminum powder, 1-3 parts of water reducing agent, 7-9 parts of lime, 10-15 parts of modified waste rubber powder, 10-12 parts of hollow glass microspheres, and 12-16 parts of modified polystyrene fibers.

2. An aerated concrete block according to claim 1, characterized in that: The method for preparing the modified waste rubber powder comprises the following steps: (1) Dispersing the waste rubber powder in a sodium hydroxide solution, stirring at a temperature of 50-55°C for 10-15 minutes, washing with water, and then dispersing it in deionized water, adding a silane coupling agent, stirring for 20-24 minutes, filtering, and drying to obtain pretreated waste rubber powder; (2) heating the nano-silica at 150-160° C. for 1-2 h, dispersing it in an ethanol solution, adding hydrochloric acid, stirring it for 1-2 h, washing it with water, and drying it to obtain pretreated nano-silica; (3) Dispersing the pretreated waste rubber powder in step (1) in deionized water, adding the pretreated nano-silicon dioxide and modified kaolin in step (2), stirring at a temperature of 80-85° C. for 2-3 h, drying, and grinding to obtain modified waste rubber powder.

3. An aerated concrete block according to claim 2, characterized in that: The mass ratio of the waste rubber powder, nano silicon dioxide and modified kaolin is 1:0.4-0.6:0.1-0.

2.

4. The aerated concrete block according to claim 2, characterized in that: The preparation method of the modified kaolin comprises the following steps: calcining kaolinite at a temperature of 800-900°C for 5-6 hours, dispersing it in deionized water, adding plant ash, acetic acid and chitosan, stirring at a temperature of 70-75°C for 1-2 hours, drying and grinding to obtain the modified kaolin.

5. The aerated concrete block according to claim 1, characterized in that: The preparation method of the modified polystyrene fiber comprises the following steps: (1) dispersing polystyrene fibers in hydrogen peroxide, stirring for 10-13 minutes, washing with water, and then dispersing in deionized water, adding fatty acid polyoxyethylene ester, stirring for 1-2 hours, filtering, and drying to obtain pretreated polystyrene fibers; (2) dispersing the loofah fibers in a sodium hydroxide solution, adding graphene, stirring at a temperature of 97-99° C. for 12-16 minutes, filtering, drying, and crushing to obtain pretreated loofah fibers; (3) Dispersing the pretreated polystyrene fiber in step (1) in deionized water, adding the pretreated loofah fiber and ethyl cellulose in step (2), stirring at a temperature of 80-85° C. for 2-3 hours, filtering, and drying to obtain modified polystyrene fiber.

6. The aerated concrete block according to claim 5, characterized in that: The mass ratio of the polystyrene fiber, the loofah fiber and the ethyl cellulose is 1:0.5-0.7:0.2-0.

3.

7. The aerated concrete block according to claim 5, characterized in that: The mass ratio of the polystyrene fiber, fatty acid polyoxyethylene ester and graphene is 1g:0.1-0.2g:10-15mg.

8. The aerated concrete block according to claim 1, characterized in that: The lime is medium-speed lime, and the calcium oxide content is ≥80% (by mass).

9. The aerated concrete block according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

10. The method for preparing an aerated concrete block according to claim 1, characterized in that: The method comprises the following steps: grinding sand, mixing it evenly with water, silicate cement and a water reducing agent, adding aluminum powder, continuing to stir, then adding lime, modified waste rubber powder, hollow glass microbeads and modified polystyrene fiber, stirring for 10-15 minutes to obtain concrete, pouring the concrete slurry into a mold, standing it for 12-14 hours, cutting it to obtain a block brick body, steaming and curing the block brick body to obtain an aerated concrete block.

Citation Information

Cited By

  • Concrete block and preparation method thereof

    CN120136504A

  • Concrete block and preparation method thereof

    CN120136504B